Cardiovascular disease prevention - who wants to live forever? - Micov, Ana (Archives of Pharmacy, 2022)
Atherosclerotic cardiovascular diseases (ASCVDs) are the leading cause of death globally. Most cardiovascular diseases can be prevented or have better clinical outcomes, by appropriate (non)pharmacological measures. According to Heraclitus’ pattern, how a person’s habits, environment, and national morbidity changed, so did the recommendations for cardiovascular disease prevention. Current guidelines of the European Society of Cardiology propose individual and population-level interventions for cardiovascular prevention in apparently healthy people (primary prevention) and patients with established ASCVD or its equivalents, such as diabetes and chronic kidney disease (secondary prevention). The cornerstone of prevention is an individual’s cardiovascular risk estimation and education on the importance of modifiable risk factor control. General preventive measures include the adoption of healthy lifestyle (smoking cessation, physical activity, Mediterranean diet, and reduced alcohol intake) and risk modifiers control (e.g., psychosocial stress). Individual-level interventions depend on the estimated cardiovascular risk and age category, with a holistic approach to patient. The higher the cardiovascular risk, the greater the benefit of risk factor treatment. The introduction of pharmacotherapy for optimal control of dyslipidemia, arterial hypertension, and/or diabetes is reserved for patients with (very) high cardiovascular risk. A stepwise treatment-intensification approach is advocated to achieve the treatment targets. The outcome of preventive measures is adversely affected by comorbidities (mental disorders, inflammatory diseases, atrial fibrillation), which should therefore be adequately treated. Policy interventions at the population level are still a weak link in most countries and should include promotion of physical activity and diet, restrictions on tobacco/alcohol consumption, and air pollution reduction.